Dengue and Zika Virus 5′ Untranslated Regions Harbor Internal Ribosomal Entry Site Functions - Yutong Song (American Society for Microbiology, 2019)
ABSTRACT The Flavivirus genus of the Flaviviridae family encompasses numerous enveloped plus-strand RNA viruses. Dengue virus (DENV), a flavivirus, is the leading cause of serious arthropod-borne disease globally. The genomes of DENV, like the genomes of yellow fever virus (YFV), West Nile fever virus (WNV), or Zika virus (ZIKV), control their translation by a 5′-terminal capping group. Three other genera of Flaviviridae are remarkable because their viruses use internal ribosomal entry sites (IRESs) to control translation, and they are not arthropod transmitted. In 2006, E. Harris’ group published work suggesting that DENV RNA does not stringently need a cap for translation. They proposed that instead DENV translation is controlled by an interplay between 5′ and 3′ termini. Here we present evidence that the DENV or ZIKV 5′ untranslated regions (5′-UTRs) alone have IRES competence. This conclusion is based, first, on the observation that uncapped monocistronic mRNAs 5′ terminated with the DENV or ZIKV 5′-UTRs can efficiently direct translation of a reporter gene in BHK and C6/36 cells and second, that either 5′-UTR placed between two reporter genes can efficiently induce expression of the downstream gene in BHK cells but not in C6/36 cells. These experiments followed observations that uncapped DENV/ZIKV genomic transcripts, 5′ terminated with pppAN… or GpppAN…, can initiate infections of mammalian (BHK) or mosquito (C6/36) cells. IRES competence of the 5′-UTRs of DENV/ZIKV raises many open questions regarding the biology and control, as well as the evolution, of insect-borne flaviviruses. IMPORTANCE Members of the genus Flavivirus of Flaviviridae are important human pathogens of great concern because they cause serious diseases, sometimes death, in human populations living in tropical, subtropical (dengue virus [DENV], Zika virus [ZIKV], and yellow fever virus), or moderate climates (West Nile virus). Flaviviruses are known to control their translation by a cap-dependent mechanism. We have observed, however, that the uncapped genomes of DENV or ZIKV can initiate infection of mammalian and insect cells. We provide evidence that the short 5′ untranslated region (5′-UTR) of DENV or ZIKV genomes can fulfill the function of an internal ribosomal entry site (IRES). This strategy frees these organisms from the cap-dependent mechanism of gene expression at an as yet unknown stage of proliferation. The data raise new questions about the biology and evolution of flaviviruses, possibly leading to new controls of flavivirus disease.